Genotype distribution of human papillomavirus among women with cervical cancer stratified by HIV status in Tanzania. - Alita Mrema; Mamsau Ngoma; Emmanuel L Lugina; Atukuzwe Kahakwa; Chacha Josiah Mwita; Salama Iddy; Eulade Rugengamizi; Kandali Samwel; John Ngowi; Salum J Lidenge; Charles Wood; Julius Mwaiselage (PLoS ONE)
Background Cervical cancer (CC) is the leading cancer among women in Tanzania, especially among those between the ages of 15 and 44. The prevalence of high-risk Human papillomavirus (HR-HPV)-16/18 women in the general population at any given time is 3.3%. HR-HPVs 16 or 18 are the primary cause of CC. The distribution of HPV genotypes among women with CC according to HIV status is unknown in Tanzania. This study aimed to determine the HPV genotype distribution according to HIV status among women with CC in Tanzania. Methods This cross-sectional study was done at Ocean Road Cancer Institute (ORCI) in Tanzania among women with histologically confirmed CC. HIV serology testing was performed. Biopsy was taken from cervical lesions, and DNA was extracted. HPV DNA was amplified by using a previously validated multiplex HPV PCR assay targeting 14 high-risk HPV genotypes (16,18,30,31,33, 35, 39, 45, 51, 52, 56, 58, 59, and 66) and two low-risk HPV genotypes (6 and 11). Continuous variables were compared using either a student t-test or the Mann-Whitney U test. Fisher's exact test was employed to compare discrete variables. A P-value less than 0.05 was considered statistically significant. Results We included 100 women with CC. The prevalence of HIV infection in this study was 42%. The prevalence of any HPV infection was 94%, ranging from 1-3 genotypes per woman. HPV. The median age for women living with HIV (WLWH) with CC patients was 45 years (IQR, 31-60), while the median age for HIV-uninfected women with CC patients was 57 years (IQR, 30-78). (p = 0.0001). WLWH and HIV-uninfected women had similar HPV prevalence, except for HPV 35, which was more common in WLWH. There was a trend of high prevalence of HPV 52 and HPV 58 in WLHH compared to HIV-uninfected women, but this difference was not statistically significant. The prevalence of HPV 16 and/or 18 infection in the entire sample was 85%. The combined prevalence of HPV 16 and/or 18 was 76% WLWH and 91% amongst HIV-uninfected women (p = 0.036).The majority of women (77.9%) had single-genotype HPV infection. There was no difference in the distribution of multiple or single HPV genotypes infection by HIV status (p = 0.25). Conclusion In this study, HIV positive women with CC presented at a significantly younger age (45 years) compared to the HIV-negative women (57 years). The prevalence of high-risk HPV is high among women with CC in Tanzania. Distribution of most high-risk HPV genotypes among women with CC was not significantly influenced by HIV status except for HPV 35, which appeared to be more in HIV positive women compared to HIV-negative women. While the majority of the high-risk HPV infections were with single HPV genotypes, the prevalence of multiple high-risk HPV infections was at 22%, with no significant difference between the two HIV statuses. A vaccination program that aptly targets HPV 16 and 18 could prevent up to 85% of CC cases in Tanzania, regardless of HIV. Keywords: Human papillomavirus, cervical cancer, HIV, Tanzania.